Pelatihan Penggunaan Website Untuk Meningkatkan Literasi Media Petani Kelapa Sawit Di Desa Kiap Jaya Kecamatan Bandar Sei Kijang Kabupaten Pelalawan Provinsi Riau - Yulida, Roza; Rosnita, Rosnita; Kurnia, Deby; Andriani, Yulia; Restuhadi, Fajar (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Kiab Jaya village has the main potential, namely oil palm, where oil palm is an agricultural sector that can provide a sizeable contribution. Palm oil farmers are one of the farmer groups incorporated in the Village Unit Cooperatives (KUD), this makes KUD to continue to produce new innovations that are able to bring the farmer groups to continue to develop, especially in supporting community welfare. Website as an information system that can provide accurate information, it can be utilized by KUD to become a media that supports the role of KUD, bringing farmer groups to be able to operate in a successful way by means of technology literacy so that farmer groups will continue to get information the latest and increase the literacy of oil palm farmers. Therefore, the purpose of this community service activity is to create a KUD Website named Koperasi Kiap Mandiri, which later will contain information about cooperatives and information about oil palm plantations, by involving the students as well as agents of change. The method of the activity is in the form of website creation training for Kukerta Students, website management training for cooperative administrators in managing websites, training in using websites for participants (cooperative members), and website launching. This activity begins with a time span from April to September 2019. The results of this activity are the formation of the cooperative website Kiap Jaya Mandiri, website module with ISBN: 978-623-7512-49-3, the formation of website managers and increased knowledge and skills about the technical use of the website , searching for information about oil palm science and technology through websites and sharing information through media websites, so as to increase media literacy in oil palm farmers.